2009
DOI: 10.1002/dat.20278
|View full text |Cite
|
Sign up to set email alerts
|

Post‐kidney transplantation erythrocytosis and its relationship to renal artery stenosis, IGF‐1, and its binding protein 3 (IGFBP‐3)

Abstract: Background Erythrocytosis is relatively common following kidney transplantation. It increases the risk of thromboembolism. Insulin‐like growth factor‐1 (IG‐1) and its binding protein 3 (IGFBP‐3) may play a role in its pathogenesis. Patients and Methods A total of 120 consecutive kidney‐transplanted patients with at least 3 month graft function were studied. Forty‐five kidney transplant patients were then selected and divided into 2 groups: 15 patients with post‐transplant erythrocytosis (PTE; group I), 30 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…A total of 61 studies underwent full-length article review; 22 were excluded, as they did not include controls or report the outcome of interest. A total of 39 observational studies [4,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47], including 7,099 patients, finally met our inclusion criteria and were included in the meta-analysis. Figure 1 outlines our search methodology and selection process; the baseline characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 61 studies underwent full-length article review; 22 were excluded, as they did not include controls or report the outcome of interest. A total of 39 observational studies [4,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47], including 7,099 patients, finally met our inclusion criteria and were included in the meta-analysis. Figure 1 outlines our search methodology and selection process; the baseline characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In this study it was found that conditions like splenectomy, anemia or immunosuppression therapies have no role in causing Erythrocytosis. The prevalence of vascular diseases like diabetes shows that it can be linked with Erythrocytosis [15][16] . As per another study it was found that PTE prevalence was more in case of women as compared to men 17 .…”
Section: Discussionmentioning
confidence: 99%